The Influence of Marketing Mix (7P) on Patient Satisfaction in Hospitals: A Literature Review - Yusron, Ahmad; Rohmah, Nur; Ningsih, Riyan (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Healthcare services in hospitals are rapidly developing. To cope with these changes, hospitals are required to implement optimal strategies to compete and adapt. Hospital marketing is becoming increasingly competitive worldwide. Marketing mix strategy is considered one of the core concepts of marketing theory. This literature review aims to analyze the effect of the marketing mix on patient satisfaction in various hospitals. The research method used in this study is a Systematic Literature Review (SLR). Search from google scholar, PubMed, google.com, Portal Garuda, with search keywords